Relationship between particulate matter and population of airborne microorganism in goat farm: A case study at Ladang Pasir Akar, Terengganu - Azman, Azid; Mazlan, A.A.; Samsudin, M.S.; Razik, M.A.; Shaharudin, S.M. (2021)
The aim of this study is to determine the concentration of particulate matter and airborne microorganism and to evaluate the relationship between particulate matter and airborne microorganism in goat farm of Pasir Akar, Terengganu, Malaysia. Aeroqual 500 series sensor was used to collect particulate matter, while DRF e-MAS was used to catch the airborne microorganism. The collected airborne microorganism was incubated in laboratory and the colony forming unit (cfu) of airborne microorganism was determined using Omeliansky's formula based on colonial observation formed after incubation. The data were analysed using descriptive analysis to gain parameter concentration and regression analysis to gain significance difference and correlation to assess the relationship between particulates and airborne microbes. As a result, any particulate matter changes will affect airborne microorganism population.